Gravity field of the orientale basin from the gravity recovery and interior laboratory mission - Zuber, M.; Smith, D.; Neumann, G.; Goossens, S.; Andrews-Hanna, J.; Head, J.; Kiefer, W.; Asmar, S.; Konopliv, A.; Lemoine, F.; Matsuyama, I.; Melosh, H.; et al. (The American Association for the Advancement of Science, 2016)
The Orientale basin is the youngest and best-preserved major impact structure on the Moon. We used the Gravity Recovery and Interior Laboratory (GRAIL) spacecraft to investigate the gravitational field of Orientale at 3- to 5-kilometer (km) horizontal resolution. A volume of at least (3.4 ± 0.2) × 106 km3 of crustal material was removed and redistributed during basin formation. There is no preserved evidence of the transient crater that would reveal the basin's maximum volume, but its diameter may now be inferred to be between 320 and 460 km. The gravity field resolves distinctive structures of Orientale's three rings and suggests the presence of faults associated with the outer two that penetrate to the mantle. The crustal structure of Orientale provides constraints on the formation of multiring basins.